THE EFFECT OF HCl CONCENTRATION ON THE SOAKING OF BROWN SEAWEED (Sargassum plagyophyllum) ON THE CHARACTERISTICS OF SODIUM ALGINATE - Tedy Kamal Sumannag; Rahman Karnila; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was aimed to determine the effect of HCl concentration on the soaking of brown seaweed Sargassum plagyophillum as a supporting material during extraction. The research method used was an experimental method that carried out alginate extracts from seaweed Sargassum plagyophylum by giving immersion treatment of HCl solution with different concentrations consisting of A0 (0% HCl); A1 (0.3%HCl); A2 (0.4%HCl); and A3 (0.5% HCl). The design used was a Completely Randomized Non-Factorial Design (CRD) with 3 replications. The analysis was measure for a yield, water content, ash content, and viscosity. The best result from this study was A3 treatment, wherein the value of the yield, moisture content, ash content, and viscosity were 14.52%, 14.23% 22.19% and 2.57cps, respectively. Keywords: HCl, Sargassum plagyophyllum, seaweed, viscosity